17β-Estradiol and the glucocorticoid clobetasol propionate affect the blood coagulation cascade in zebrafish. (April 2020) - Schmid, Simon; Fent, Karl
Abstract: Fish are exposed to estrogens, progestins and glucocorticoids in the aquatic environment but effects on the blood coagulation cascade are unknown. Here we analyzed effects of 17β-estradiol (E2) alone and in combination with mixtures of new generation progestins and the glucocorticoid clobetasol propionate (CLO) in zebrafish embryos to assess their effects on the blood coagulation system. We assessed transcripts of 13 genes, such as coagulation factors, and genes involved in the anticoagulation and fibrinolytic system upon exposure to concentrations of 0.01-10 μg/L at 144 h post fertilization. Transcripts of genes encoding coagulation factors VII, X and fibrinogen, as well as protein C from the anticoagulation system, and serpine1 from the fibrinolytic system were upregulated by 10 μg/L, and factor II by 1 μg/L E2, as well as in mixtures containing E2 with progestins. CLO alone or in mixtures with progestins and E2 induced genes encoding factor VII, IX and fibrinogen. Progestins induced expression of genes encoding factor IX ( f9b ) only, but in mixtures with E2 and CLO, also factor VII ( f7 ) and fibrinogen ( fga ) were induced. Our study demonstrates that exogenous exposure to E2 and CLO alone and in mixtures with new generation progestins used in contraception alter the expression of blood coagulation genes. This ultimately may lead to adverse effects on blood coagulation in fish. Graphical abstract: Image 1 Highlights: E2 and its mixture with progestins and CLO on 13 blood coagulation genes were assessed. E2 induced transcripts of coagulation factors VII, X and II, fibrinogen, protein C and serpine1 . CLO alone and in mixtures induced transcripts of factor VII, IX and fibrinogen. Progestins had little effects but led to transcriptional induction of gene encoding factor IX ( f9b ). Estrogens and glucocorticoids may affect the blood coagulation cascade in fish. Abstract : Estradiol and clobetasol propionate alter expression of genes in the blood coagulation cascade.